Efisiensi termal mesin pengering egg tray tipe rak - Pramitasari, Retno Eka; Basuki, Basuki; Rokhmah Wati, Dian Anisa; Irfa'i, Mochamad Arif; Rosadi, Mohammad Munib (Universitas Muria Kudus, 2023)
Drying is a process that aims to prevent decay. However, the natural drying process can produce less than optimal results, especially during the rainy season. Uncertainty about the use of solar energy triggers to conduct this research. In addition, it takes a long time and requires a large area during the drying process, so this research aims to provide a more optimal value in terms of efficiency by using a rack-type egg tray drying machine. The dimensions of the shelf-type egg tray drying cabinet are 500 x 500 x 900 and a control box. The heating elements are arranged in parallel consisting of 3 tubular heating elements. The thermal efficiency generated in the rack type egg tray drying machine with an average thermal efficiency value of 32.18% and the highest thermal efficiency value produced on the first rack reached 38.32%